SYSTEMIC APPROACH TO THE PSYCHOLOGICAL ANALYSIS OF IT PROFESSIONALS’ OCCUPATIONAL ACTIVITY: THEORETICAL AND METHODOLOGICAL ASPECTS (Psychology Travelogs, 2025)
This article presents a comprehensive theoretical and methodological analysis of the psychological features of IT professionals’ occupational activity. The study focuses on the relevance of psychological assessment and professional selection in the IT field, which is characterized by rapid technological change, high cognitive demands, and increasing mental workload. The authors examine and systematize modern conceptual approaches to the psychological analysis of professional activity, including functional-algorithmic, structural, structural-algorithmic, generalized structural, structural-psychological, and integrative models of mental activity. These models serve as a foundation for understanding the operational, motivational, and regulatory aspects of professional performance in the IT sphere. The study identifies and classifies thirteen groups of psychological methods used in professional analysis, such as the study of official documentation, observation, interviews, modeling, algorithmic and temporal analysis of tasks, and psychophysiological experimentation. Special emphasis is placed on the application of systemic profesiography, which enables the integrated study of working conditions, mental demands, and psychological characteristics of the professional environment. This approach allows for the identification of key factors influencing professional suitability, psychological well-being, and long-term efficiency of IT specialists. The research also outlines the importance of evaluating both stable and developable psychological traits when making decisions about personnel recruitment, training, and development in the IT industry. The findings contribute to the development of methodological frameworks for improving professional selection procedures and psychological support for IT professionals, ensuring better alignment between personal capabilities and professional requirements.
Keywords: psychological analysis; IT specialist; professionalography; methodological techniques; professional psychological selection